Agenda 21 [compact disc, unabridged] - Beck, Glenn (Simon & Schuster Audio, 2012)
After the worldwide implementation of a UN-lead program called Agenda 21, America is known simply as the 'Republic.' There is no president, congress, Supreme Court, or freedom--only authorities. This bleak existence is all 18-year-old Emmeline has ever known. Like most citizens, her only goals are to create energy and new human life, until the day they came for her mother. Soon, Emmeline begins to search for the truth, and realizes she is up against more than she ever thought.